2002
DOI: 10.1034/j.1600-0501.2002.130201.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing around implants and teeth with healthy or inflamed peri‐implant mucosa/gingiva

Abstract: The purpose of this study was to obtain a better understanding of probing measurements around osseointegrated oral implants. A comparison was made of probe tip position around Astra Tech implants and teeth of eight cynomolgus monkeys (Macaca fascicularis) in conditions of i) healthy peri-implant mucosa/gingiva, ii) mild mucositis/gingivitis, iii) severe mucositis/gingivitis or iv) peri-implantitis/periodontitis. Histological sections of 128 probes that were attached to implants or teeth with surrounding tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 54 publications
7
132
1
8
Order By: Relevance
“…Gallucci, Belser, Bernard and Magne (2004) found mesial and distal PD often ranging between 4 and 8 mm depending on how scalloped the mucosa is. Animal studies have shown that conditions of mild inflammation already yield deeper pockets around implants compared to teeth and this does not necessarily coincide with actual bone loss (Schou et al., 2002). A multilevel analysis performed in a group of 52 patients with screw‐retained restorations on 92 implants revealed that deeper PD is associated with higher tendency to bleed.…”
Section: Introductionmentioning
confidence: 99%
“…Gallucci, Belser, Bernard and Magne (2004) found mesial and distal PD often ranging between 4 and 8 mm depending on how scalloped the mucosa is. Animal studies have shown that conditions of mild inflammation already yield deeper pockets around implants compared to teeth and this does not necessarily coincide with actual bone loss (Schou et al., 2002). A multilevel analysis performed in a group of 52 patients with screw‐retained restorations on 92 implants revealed that deeper PD is associated with higher tendency to bleed.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda standart kuvvet uygulanarak yapılan ölçümler arasında oluşan farkın, implant çevresi mukozanın sondalama ile oluşabilecek delinmelere karşı daha dirençsiz olması ile açık-lanabilir 19 . Bu dirençsizliğin ana nedenlerinden biri ise alveol kemik kreti üstü bağ dokusundaki kollagen liflerin implant yüzeyine paralel konumlanması 19,23,24 olabilir. Yumuşak dokunun direnci implant çevresi mukoza ve implant yü-zeyi arasındaki bağlantının pozisyonu ve organizasyonundan da etkilenmektedir.…”
Section: Discussionunclassified
“…Yumuşak dokunun direnci implant çevresi mukoza ve implant yü-zeyi arasındaki bağlantının pozisyonu ve organizasyonundan da etkilenmektedir. 19,23,24 Çalışmamızda, implant grubunda SK görünen bölge sayısı doğal dişler grubuna oranla daha fazla bulunmuştur. Klinik ölçümlerde standart kuvvet uygulandığı için SK'nin travmatik neden ile oluşmadığı düşünülmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Serino et al reported that measurements of peri-implantitis associated with prosthetic reconstruction implants generated in situ should be interpreted cautiously with regard to their ability to determine the severity of bone loss at implants 31) . Qualitatively, radiographic evaluation revealed that PD tended to be proportional to MBL, because the probe tip penetrated to a position closer to the alveolar bone crest in sites with peri-implant disease 32,33) . However, no relationship existed between macroscopic and radiographic evaluations in this experiment, because the bone loss appeared around the deep site of the implant, and was not detectable using a periodontal probe.…”
Section: Discussionmentioning
confidence: 99%